Marxism and Capitalism in the 21st Century: A Comparative Study - Magar, Rudra Bahadur Pulami (Kanya Journal, 2025)
This research article, titled "Marxism and Capitalism in the 21st Century: A Comparative Study", critically analyzes the continued dominance of capitalist structures in the contemporary world and the significances associated with them. The research shows that while capitalism has made remarkable achievements in technology, production, and economic expansion, it has institutionalized inequality, worker insecurity, environmental crises, and capitalist control over the democratic process. Methodologically, the manuscript adopted a qualitative, descriptive, and comparative approach, relying exclusively on secondary sources such as books, journal articles, and credible academic reports. The dominance of multinational corporations and international financial institutions in developing countries has created new forms of dependency and inequality, which Marxists understand as neo-colonialism. In addition, the profit-oriented nature of capitalist structures has accelerated climate change and the depletion of natural resources, which poses serious challenges to environmental justice. Marxists view these problems as impossible to solve through reformist or technological means alone, and point to the need for structural change. The labor movement, alternative politics, and environmental justice movements have intensified the ideological and practical challenge to capitalism. This research concludes that while capitalism is still dominant, its internal contradictions have made the search for alternative models inevitable. It argues that social justice, equality, participatory democracy, and long-term solutions to environmental challenges can be found.